Implementation of Hypnoteaching in English Language Teaching (ELT) - Tira Nur Fitria (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
This research discusses the implementation of hypnoteaching in the teaching and learning process. This research is library research. The analysis shows several steps in implementing hypnoteaching: 1) Giving intentions and motivation. It is related to the teacher mastering the material and continuing to provide meaning to the things that are conveyed. 2) Pacing. Pacing is stepping/equalizing positions, gestures, language, and brain waves between teachers and students. 3) Leading. Leading is directing the class atmosphere to create a conducive and efficient manner, but still feel calm or relaxed. 4) Giving praise. Praise is a self-esteem boost and forms a person's self-concept so it is very important to provide sincere praise to students. 5) Modeling. Modeling is being a role model and setting an example through speech and behavior. Besides, teachers should consider using hypnoteaching including the teacher’s appearance, feeling of sympathy, empathic attitude, language use, demonstration, or issuing self-expression for the kinesthetic, and motivating learners. However, the teacher's proficiency in using hypnoteaching depends on the extent to which the teacher uses, applies, and practices their knowledge in the learning process. Hypnoteaching places more emphasis on the abilities of the subconscious brain than the student's conscious brain. By using hypnoteaching, teachers can create a variety of learning processes, the learning process will run dynamically, there is good interaction between teachers and students, students are more motivated to learn and understand the learning material, students enjoy learning activities, also there are positive suggestions for the subconscious language used by teachers.